2019
DOI: 10.1039/c9ta04145a
|View full text |Cite
|
Sign up to set email alerts
|

Bi3+ doped 2D Ruddlesden–Popper organic lead halide perovskites

Abstract: 2D Ruddlesden–Popper perovskites exhibit flexible light-emitting modulations and surprising stability improvements upon heterovalent Bi3+ doping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The vast potential for tuning the optical and electronic properties of 2D perovskites by varying their elemental composition (e.g., the choice of metals, halides, and small organic cations), organic spacers, and number of layers (i.e., thickness) holds considerable promise for further system optimization. Additionally, charge-carrier collection can be supported through optimized deposition and process engineering, , additive engineering (e.g., SCN – and MACl), and doping approaches that favor vertical growth and preferential out-of-plane charge transport. In fact, the current certified power conversion efficiency (PCE) record for 2D perovskite solar cells in conventional structures is 16.6%, which is still much lower than that for 3D perovskite solar cells.…”
mentioning
confidence: 99%
“…The vast potential for tuning the optical and electronic properties of 2D perovskites by varying their elemental composition (e.g., the choice of metals, halides, and small organic cations), organic spacers, and number of layers (i.e., thickness) holds considerable promise for further system optimization. Additionally, charge-carrier collection can be supported through optimized deposition and process engineering, , additive engineering (e.g., SCN – and MACl), and doping approaches that favor vertical growth and preferential out-of-plane charge transport. In fact, the current certified power conversion efficiency (PCE) record for 2D perovskite solar cells in conventional structures is 16.6%, which is still much lower than that for 3D perovskite solar cells.…”
mentioning
confidence: 99%
“…Lin et al reported the rst series of heterovalentdoped 2D RPs via Bi 3+ doping for (BA) 2 (MA) nÀ1 Pb n I 3n+1 86. Similar to the earlier case, Bi 3+ doping did not signicantly impact the crystal structures as the average Bi-I bond length in the BiI 6…”
mentioning
confidence: 62%
“…3À octahedron (3.07 Å) is very close to the Pb-I bond length in (BA) 2 (MA) nÀ1 Pb n I 3n+1 crystals (3.18 Å for n ¼ 1, 3.16 Åfor n ¼ 2, 3.14 Å for n ¼ 3) 86. Dang et al synthesized Li doped (PEA) 2 PbBr 4 perovskite crystals using a solution-processing method 87.…”
mentioning
confidence: 78%
See 2 more Smart Citations